2020
DOI: 10.1519/jsc.0000000000003931
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Warming Up on Achilles Tendon Blood Flow and Stiffness

Abstract: Acute effects of warming up on Achilles tendon blood flow and stiffness. J Strength Cond Res 36(10): 2717-2724, 2022-The aim of this study was to investigate the acute effect of frequently used warm-up exercises on the Achilles tendon blood flow and stiffness. In doing so, we want to explore which exercises are suitable to properly prepare the athlete's Achilles tendon in withstanding high amounts of loading during sport activities. This knowledge could help sport physicians and physiotherapists when recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Our study (Figures 3, 4) and previous studies reported MDCs for PT and AT stiffness and length measurements using the myotonometry method (12,13,15) and the EFOV-US technique (19,20), respectively. With regard to the results of previous studies investigating changes in PT and AT stiffness (31,(48)(49)(50)(51)(52)(53) and length (34, 36-38, 43, 44, 54) in sports and medicine, these changes could be detected outside the measurement error using myotonometry and the EFOV-US technique, which supports the practical applicability of both technologies. For future studies using the EFOV-US technique, and as conducted here, we recommend the usage of a fixable brace to avoid axial shifts of the US probe.…”
Section: Clinical and Practical Implicationssupporting
confidence: 65%
“…Our study (Figures 3, 4) and previous studies reported MDCs for PT and AT stiffness and length measurements using the myotonometry method (12,13,15) and the EFOV-US technique (19,20), respectively. With regard to the results of previous studies investigating changes in PT and AT stiffness (31,(48)(49)(50)(51)(52)(53) and length (34, 36-38, 43, 44, 54) in sports and medicine, these changes could be detected outside the measurement error using myotonometry and the EFOV-US technique, which supports the practical applicability of both technologies. For future studies using the EFOV-US technique, and as conducted here, we recommend the usage of a fixable brace to avoid axial shifts of the US probe.…”
Section: Clinical and Practical Implicationssupporting
confidence: 65%
“…The results of the literature search are illustrated in Fig. 1 , with a total of 38 studies 26 , 27 , 30 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ( n = 1134 participants, male = 567, female = 415, and 4 studies including 152 participants without information regarding sex; 27 , 39 , 40 , 41 ES: n = 140) meeting the inclusion criteria. Of these, 25 papers compared the effects of stretching to those of alternative activities on ROM; 27 , 39 , 40 , 41 , 42 , 43 , 45 , 46 , 48 , 49 , 51 , 54 , 55 , 57 , 58 , 59 , 60 ,…”
Section: Resultsmentioning
confidence: 99%
“…Although there is no specific parkour-related literature on how to warm-up, a more generic literature can bring some clues. To properly prepare the musculo-skeletal system, and especially lower limb tendons for high plyometric activities, it was shown very recently that warm-up should include sufficient mechanical stress by performing intensive exercise (Pieters et al, 2020), and that stretching or light joint mobility was inefficient or even deleterious. Regarding stretching habits specifically, around 20% of participants reported to stretch before parkour training or during the warm-up.…”
Section: Discussionmentioning
confidence: 99%
“…Besides inherent physiological factors, the training organization and personal habits also represent an important risk of injury. Especially the presence and importance of warm-up is often reported as an important factor of injury risk particularly in the lower limb (Pieters, Wezenbeek, De Ridder, Witvrouw, & Willems, 2020). Since traceurs must manage important physical constraints, it can also easily be argued that without a proper physical preparation the traceur is exposed to a significantly higher risk of injury.…”
Section: Evaluation Of Intrinsic Factorsmentioning
confidence: 99%